PENGARUH PEMERIKSAAN INTERIM, LINGKUP AUDIT DAN INDEPENDENSI TERHADAP PERTIMBGAN OPINI AUDITOR (STUDI KASUS PADA BPK RI PERWAKILAN PROVINSI JAWA TIMUR) - Fitri Wirda Zahara; Hj. Maslichah (Universitas Islam Malang, 2017)
ABSTRACTThis study aims to analyze the effect of interim audit, scope of audit, and independency on auditor judgements of auditors of BPK RI Jawa Timur Province Representatives. This study uses primary data through a questionnaire with Likert scale. Sampling method used is purposive sampling. The sample in this research were as many as eighty respondents. Test the quality of data use in this research is the reliability test using Cronbach alpha and test the validity of using the Pearson correlation and hypothesis testing using multiple regression analysis using SPSS 17.0. The Result processing and analysis of data from this study are: (a) interim audit has significant positive effect on auditor judgements, (b) scope of audit has significant positive effect on auditor judgements, (c) independency has significant positive effect on auditor judgements, (d) interim audit, scope of audit and independency influence auditor judgements simultaneously.Keywords: Interim Audit, Scope of Audit, Independency and Auditor Judgements